A Critical Analysis of Reporting in Systematic Reviews and Meta-Analyses in the Peyronie's Disease Literature. Issue 4 (14th February 2022) - Bole, Raevti; Gottlich, Harrison Chase; Ziegelmann, Matthew J.; Corrigan, Dillon; Levine, Laurence A.; Mulhall, John P.; Bajic, Petar
ABSTRACT: Background: Despite an increasing number of publications on Peyronie's disease (PD), evidence-based clinical decision-making remains challenging due to the small number of well-designed clinical trials. Aim: To perform a critical analysis of reporting quality in PD systematic reviews (SR) and meta-analyses (MA). Methods: Study protocol registration was performed on the Open Science Framework platform. In January 2021, a systematic electronic search of the Medline/PubMed, Embase, Ovid, Scopus, Joanne Briggs Institute, and Cochrane databases was performed. Search terms included "Peyronie's disease" and "systematic review OR meta-analysis OR meta-analysis." Eligibility criteria were English-language, relevance to PD and specification of "systematic review" or "meta-analysis" in the title or abstract. Oxford Center for Evidence-Based Medicine levels of evidence were used to classify original studies reviewed within each publication. Risk of bias was assessed using the ROBIS tool. Data were tabulated and reported as means with standard deviation, median with interquartile range and t -testing as appropriate. Strength of association between variables was calculated using Pearson correlation coefficient. Statistical analyses were performed on RStudio (version 1.4.1106). Outcomes: Outcomes included review type, level of evidence, authorship, journal, publication date, "A MeaSurement Tool to Assess systematic Reviews" (AMSTAR-2) score and "Preferred Reporting Items for Systematic Reviews and Meta-Analyses" (PRISMA) score. Results: From 1974 to 2021, 340 articles were identified. After review, 17 full length articles were included. Thirteen were SR, 2 MA and 2 was combined. Significant heterogeneity was seen in evidence level of included studies. There was median 54% adherence to AMSTAR-2 criteria and 74% adherence to PRISMA criteria. Overall AMSTAR-2 confidence rating was Critically Low in 11 of 17 studies. Correlation analysis revealed very high positive association between AMSTAR 2 and PRISMA adherence (+0.95). ROBIS revealed "High" concern regarding methods used to collect data and appraise 12/17 studies (71%), and "High" concern regarding synthesis and findings in 8 of 17 studies (47%). Clinical Implications: Many SR include markedly heterogenous levels of evidence and fail to meet accepted methodological criteria for reporting. Strengths and Limitations: Main strengths include extensive literature review and analysis of standardized study reporting. One limitation is that aggregate scoring of AMSTAR-2 and PRISMA is not intended as primary method of quality assessment; however effect was minimized by reporting critical domains, overall quality assessments and specifics on globally poorly reported domains. Conclusion: More high quality randomized controlled PD trials are necessary; SR and MA should focus on these studies alone.